One-year recurrence rate of new-onset atrial fibrillation after acute myocardial infarction - Alicia Prieto-Lobato; Víctor Hidalgo Olivares; Manuel Gerónimo Pardo; Marta Cubells Pastor; Francisco Manuel Salmerón Martínez; Miguel José Corbí-Pascual (Revista Portuguesa de Cardiologia)
Introduction and objectives: Atrial fibrillation (AF) is the most common cardiac arrhythmia worldwide, with a prevalence of up to 21% in the early phase of acute myocardial infarction (AMI). Data on new-onset AF in this context are limited, and long-term prognosis remains unclear. Methods: We conducted a retrospective observational cohort study from December 2011 to May 2021, including patients who experienced a first episode of paroxysmal AF during hospitalization for AMI. The primary outcome was the recurrence of AF within the first year post-discharge. Secondary outcomes included all-cause mortality, cardiovascular mortality, and a composite of major adverse cardiovascular events. Results: A total of 209 patients were included. There was AF recurrence in 19 patients, 9.1% (95% CI 5.2–13.0%) with a median time to recurrence of 84 days (interquartile range 27.5–157.5). While mortality in the AF recurrence group was numerically higher than in the non-AF recurrence group, this difference did not achieve statistical significance (15.8% vs. 7.4%, p=0.19). Patients with AF recurrence had significantly worse prognosis (47.4% vs. 23.7%, p=0.04), primarily due to increased heart failure (HF) hospitalizations. Conclusions: In patients with a first episode of paroxysmal AF during AMI, one-year recurrence is relatively low (9.1%); however, AF recurrence is associated with significantly worse prognosis, driven largely by HF hospitalizations. Resumo: Introdução e objetivos: A fibrilhação auricular (FA) é a arritmia cardíaca mais comum a nível mundial, com uma prevalência de até 21% na fase inicial do enfarte agudo do miocárdio (EAM). Os dados relativos à FA de início recente neste contexto são limitados, e o seu prognóstico a longo prazo permanece incerto. Métodos: Realizámos um estudo de coorte observacional retrospetivo entre dezembro de 2011 e maio de 2021, incluindo doentes que apresentaram um primeiro episódio de FA paroxística durante a hospitalização por EAM. O resultado primário foi a taxa de recorrência de FA no primeiro ano após a alta hospitalar. Os resultados secundários incluíram mortalidade por todas as causas, mortalidade cardiovascular e um composto de eventos cardiovasculares adversos major. Resultados: Um total de 209 doentes foi incluído. A recorrência de FA ocorreu em 19 doentes (9,1%, IC 95% 5,2-13,0%), com um tempo mediano até à recorrência de 84 dias [IQR 27,5-157,5]. Apesar da mortalidade no grupo com recorrência de FA ter sido numericamente superior à do grupo sem recorrência de FA, essa diferença não alcançou significância estatística (15,8% vs. 7,4%, p = 0,19). Os doentes com recorrência de FA apresentaram um prognóstico significativamente pior (47,4% versus 23,7%; p = 0,04), principalmente devido ao aumento das hospitalizações por insuficiência cardíaca. Conclusões: Em doentes com um primeiro episódio de FA paroxística durante o EAM, a taxa de recorrência em um ano é relativamente baixa (9,1%), mas a recorrência de FA está associada a um prognóstico significativamente pior, principalmente devido ao aumento das hospitalizações por insuficiência cardíaca.